IMPLEMENTASI METODE PROMETHEE UNTUK MENENTUKAN PENERIMA BEASISWA - Ichsan Taufik; Undang Syaripudin; Jumadi Jumadi (JURNAL ISTEK, 2017)
Providing scholarships at a college is usually given every year even every semester by the number and variety of donors scholarship, this may cause problems in selecting awardees so we need a system that can select students to receive a scholarship. One method is a method of decision support systems Promethee (Preference Ranking Organization Method for Enrichment Evaluation). Promethee is a method of determining the order or priority in multicriteria analysis. From the assessment of priority used in outranking relationship, where to indicate their priorities and preferences for each criterion these methods focus on the value (value) without thinking about the method of calculation. This study can provide a solution in the form of recommendations for the selection of appropriate candidates receive scholarships per department based on criteria supplied (father's occupation, mother's occupation, the number of parents income, number of dependent elderly people, home ownership, active organization).